2019
DOI: 10.3390/agronomy9120864
|View full text |Cite
|
Sign up to set email alerts
|

Ground Truthing and Physiological Validation of Vis-NIR Spectral Indices for Early Diagnosis of Nitrogen Deficiency in cv. Barbera (Vitis vinifera L.) Grapevines

Abstract: Several narrow or broadband spectral indices can be calculated at varying spatial and spectral resolution, which can then be correlated with the physiological and nutritional status of the leaves. In a three-year trial carried out on fruiting, potted cv. Barbera grapevines subjected to full (N+) or no (N0) nitrogen supply, seasonal evolution of different leaf spectral indices were correlated with non-destructive chlorophyll readings (Minolta SPAD meter), leaf gas exchange, and vine performance. Throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Small dots represent the individual logFC for each metabolite photosynthetic rates. On a methodological basis, it is confirmed that SPAD readings and A rates might show relatively poor correlation, especially when SPAD readings are above the 25 units (Squeri et al 2019;Steele et al 2008). The most significant leaf A response observed in our study was that, across leaf position and over a total leaf age span from about 30 to 125 days, N0 maintained A rates quite similar to the N + plants.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Small dots represent the individual logFC for each metabolite photosynthetic rates. On a methodological basis, it is confirmed that SPAD readings and A rates might show relatively poor correlation, especially when SPAD readings are above the 25 units (Squeri et al 2019;Steele et al 2008). The most significant leaf A response observed in our study was that, across leaf position and over a total leaf age span from about 30 to 125 days, N0 maintained A rates quite similar to the N + plants.…”
Section: Discussionsupporting
confidence: 69%
“…Leaf N concentration assessed pre-veraison in N0 was decreased by 28%, to a leaf concentration of 1.66%. According to literature (Keller and Hrazdina, 1998;Paul Schreiner et al 2013;Squeri et al 2019) this value is below the warning threshold of about 1.80% that should be warranted at that phenological stage.…”
Section: Discussionmentioning
confidence: 84%
“…Interpretation of the R 2 data reported in Table 3 vs. means, range of variation and coefficient of variation (CV) of agronomic and physiological variables is quite puzzling. In general terms, for a given index, closer correlation is expected any time a given variable, primarily due to soil heterogeneity, shows a larger degree of variability ( Trought et al, 2008 ; Baluja et al, 2013 ; Squeri et al, 2019 ; Gatti et al, 2021 ). This concept seems to hold, for instance, when RVI, NDVI3, SR680, and EVI2 are correlated with Ψ pd and Ψ md .…”
Section: Discussionmentioning
confidence: 96%
“…This was quite interesting as it indicated that N leaf could act as a diagnostic tool to identify vigor levels. Recent work by Squeri et al (2019) has ascertained that several broadband VIS-NIR indices can be profitably used for non-destructive estimates of N leaf concentration therefore making the procedure fast and effective.…”
Section: Discussionmentioning
confidence: 99%